A Collision Tumor Involving a Primary Leiomyosarcoma of the Lower Extremity and a Metastatic Medullary Thyroid Carcinoma: A Case Report. Issue 4 (October 2017) - Austin, Daniel C.; Wu, Jim S.; Spentzos, Dimitrios; Goldsmith, Jeffrey D.; Anderson, Megan E.
Abstract : Case: A 49-year-old man presented with a rapidly growing thigh mass. Histologic analyses demonstrated separate regions that were consistent with a collision tumor composed of a primary leiomyosarcoma and a metastatic medullary thyroid carcinoma. After responding to chemotherapy, the patient underwent resection of the tumor and a total thyroidectomy; he was disease-free 9 years after the diagnosis. Conclusion: A wide diagnostic differential and thorough histologic analysis are necessary in patients presenting with neoplasms of the extremities. A leiomyosarcoma may be a hospitable location for metastatic disease, and the presence of a collision tumor should be considered when pathology findings are equivocal.